Uji Efektivitas Etanol Daun Pandan (Panandus amarylifolius Roxb) Sebagai Penyembuhan Luka Sayat pada Tikus Putih (Rattus norvegicus) - Priska C. Londoran; Jabes W. Kanter; Christel N. Sambou; Hariyadi Hariyadi (Journal of Pharmaceutical and Sciences, 2023)
An incision is a wound that splits the skin area due to being cut by a sharp object. Indonesian people use medicinal plants very much in traditional or modern medicine. One of the plants that can be used as a medicinal ingredient is fragrant pandan leaves which can accelerate the wound healing process. This study aims to determine the level of effectiveness of pandan leaf extract as a healer for cuts. This study used 15 white rats which were then slashed on their backs using a 1 cm long scalpel with a depth of ± 2 mm. This study used a laboratory experiment using a completely randomized design consisting of 5 treatment groups, including 1 negative control, positive control (10 percent povidone iodine) and 3 graded concentrations, namely pandan leaf extract concentrations of 5.10 to 15 percent with 2 each. repetition times. The results of measuring the length of the wound in rats showed that fragrant pandan leaf extract with a concentration of 10 percent and 15 percent had the same effectiveness.